Pengaruh Efektifitas Penyidikan Oleh Penyidik Terhadap Kecepatan Penyelesaian Perkara Dipengadilan Pidana - Regyta Cahyani; Regita Merlandri; Vinda Milsyi Almeira (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This study examines the influence of the effectiveness of criminal investigations conducted by investigators on the speed of case resolution in criminal courts as a crucial legal issue in achieving legal certainty and judicial efficiency. The central legal questions addressed are: why some criminal cases take a long time to be resolved in court despite the completion of investigations, and how the effectiveness of investigations affects the pace of case resolution. The research problems are formulated as follows: (1) Why has the effectiveness of investigations by investigators not been optimal in accelerating case resolution in criminal courts? (2) How does the effectiveness of investigations by investigators influence the speed of case resolution in criminal courts? The research employs a normative juridical method based on Peter Mahmud Marzuki’s Legal Research, using statutory and conceptual approaches. Data were obtained from primary, secondary, and tertiary legal materials and analyzed qualitatively. The findings reveal that high investigation effectiveness characterized by the completeness of evidence, inter-agency coordination, and compliance with procedural time limits significantly accelerates court proceedings and reduces trial delays. However, structural factors such as case load and court capacity moderate this relationship. The implications suggest the need for enhancing investigator resources, improving institutional coordination, and establishing monitoring mechanisms for investigations to optimize the speed of case resolution in criminal courts.